2021
DOI: 10.1021/acs.accounts.1c00215
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Designed Nanoscale Materials for Controlling Cellular Processes

Abstract: Conspectus Nanoparticles are widely used in various biomedical applications as drug delivery carriers, imaging probes, single-molecule tracking/detection probes, artificial chaperones for inhibiting protein aggregation, and photodynamic therapy materials. One key parameter of these applications is the ability of the nanoparticles to enter into the cell cytoplasm, target different subcellular compartments, and control intracellular processes. This is particularly the case because nanoparticles are designed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 71 publications
(218 reference statements)
2
51
0
Order By: Relevance
“…Experimentally, the internalization of nanosized materials is a complex process that involves direct membrane penetration with NPs free in the cytosol and endocytotic uptake via biomembrane-coated vesicles, requiring NP sizes in the range of 10–100 nm [ 63 , 64 , 65 ]. The presence of highly reactive Fe-rich and Hg NPs ≤ 10 nm inside brain cells brings up the transportation pathway discussed by Panja and Jana [ 65 ]: arginine-terminated Au ≤10 nm enters via energy-independent direct membrane penetration and, as the size increases, there is a switch to energy-dependent endocytotic uptake. A critical issue at stake involves the fetal brain endothelial and pericyte tight junctions (TJs) and lysosomal NPs’ accumulation at PCW 8–15 weeks, potentially impacting the brain–blood barrier (BBB) formation, its regulation, and permeability [ 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, the internalization of nanosized materials is a complex process that involves direct membrane penetration with NPs free in the cytosol and endocytotic uptake via biomembrane-coated vesicles, requiring NP sizes in the range of 10–100 nm [ 63 , 64 , 65 ]. The presence of highly reactive Fe-rich and Hg NPs ≤ 10 nm inside brain cells brings up the transportation pathway discussed by Panja and Jana [ 65 ]: arginine-terminated Au ≤10 nm enters via energy-independent direct membrane penetration and, as the size increases, there is a switch to energy-dependent endocytotic uptake. A critical issue at stake involves the fetal brain endothelial and pericyte tight junctions (TJs) and lysosomal NPs’ accumulation at PCW 8–15 weeks, potentially impacting the brain–blood barrier (BBB) formation, its regulation, and permeability [ 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…We selected a coating that provides zwitterionic surface charge, as this offers good cell uptake without appreciable cytotoxicity. 42,43…”
Section: Resultsmentioning
confidence: 99%
“…We have extensively studied and applied this polyacrylate coating on different nanoparticles. 42,43 We have shown that this coating does not convert nanoparticles to organometallic compounds, and the nanoparticles are stable in the cell culture media without any precipitation (ESI, † Fig. S8).…”
Section: Oxygen Deficient Zno Nanoparticle-based Cell Therapy Under D...mentioning
confidence: 99%
See 1 more Smart Citation
“…During the last years, increased knowledge of endocytic processes allowed the design of “smarter” nanoparticles with improved targeting properties [ 13 , 107 ]. Nanoparticles with a size ranging from 100 to 500 nm are usually internalized through a clathrin-dependent endocytosis pathway [ 108 , 109 ].…”
Section: The Pharmacokinetics (Pk) and Pharmacodynamics (Pd) Properti...mentioning
confidence: 99%